International relations : perspectives, controversies and readings - Shimko, Keith L. , 1962- (Cengage Learning, 2016)
Features coverage of key principles of international relations, providing a thorough introduction to the discipline while avoiding excessive detail and complexity. This book explores essential concepts such as power politics, war and democracy, human nature, free trade, inequality, globalization, humanitarian intervention, and terrorism